The purple island, or, The isle of man - Fletcher, Phineas, 1582-1650 (Renaissance Society of America texts and studies series ;, 2017)
Phineas Fletcher?s epic allegorical poem 'The Purple Island' (1633) combines anatomical and devotional perspectives on the self as the poet explores the relationship between body and soul. The titular island is figured as both body and as England, thus merging religious, corporeal, devotional, and geo-national narratives. The present critical edition offers the first fresh editorial approach to the poem in over a century and situates the poem in its historical and critical contexts. Although the poem has often been regarded as a bizarre and fragmented curiosity, Johnathan H. Pope compellingly argues in favour of a more unified reading and understanding of the text as a whole, offering a newly-annotated edition that illuminates the text for both the Fletcher specialist and newcomer alike.